Bayesian approach for analysis of time-to-event data in plant biology - Humplík, Jan F; Dostál, Jakub; Ugena, Lydia; Spíchal, Lukáš; De Diego, Nuria; Vencálek, Ondřej; Fürst, Tomáš (Plant methods, 2020)
BACKGROUND: Plants, like all living organisms, metamorphose their bodies during their lifetime. All the developmental and growth events in a plant's life are connected to specific points in time, be it seed germination, seedling emergence, the appearance of the first leaf, heading, flowering, fruit ripening, wilting, or death. The onset of automated phenotyping methods has brought an explosion of such time-to-event data. Unfortunately, it has not been matched by an explosion of adequate data analysis methods. RESULTS AND DISCUSSION: In this paper, we introduce the Bayesian approach towards time-to-event data in plant biology. As a model example, we use seedling emergence data of maize under control and stress conditions but the Bayesian approach is suitable for any time-to-event data (see the examples above). In the proposed framework, we are able to answer key questions regarding plant emergence such as these: (1) Do seedlings treated with compound A emerge earlier than the control seedlings? (2) What is the probability of compound A increasing seedling emergence by at least 5 percent? CONCLUSION: Proper data analysis is a fundamental task of general interest in life sciences. Here, we present a novel method for the analysis of time-to-event data which is applicable to many plant developmental parameters measured in field or in laboratory conditions. In contrast to recent and classical approaches, our Bayesian computational method properly handles uncertainty in time-to-event data and it is capable to reliably answer questions that are difficult to address by classical methods.
Keywords: Bayesian inference; Uncertainty; Statistics; Time-to-event data; Plant development; Data analysis; Plant phenotyping; Survival analysis